A bibliography of James T. Farrell's writings, 1921-1957. - Branch, Edgar Marquess, 1913-2006 (University of Pennsylvania Press, 1959)
"I need an audience--so watch out!" With these James T. Farrell announced his intention of becoming a writer. He was to realize this ambition in manifold ways through his prolificacy, versatility, and his achieved recognition as a formidable figure in American literature. The material contained in this book grew out of initial research for a critical study which disclosed the chaotic state of Farrell's literary affairs and the urgent need for a bibliography. The task was not to be an easy one, for many of Farrell's writings were printed in obscure publications both in the United States and abroad. Edgar M. Branch has ferreted out, producing his compilation with enthusiasm and accuracy. This book is a definitive guide to Farrell's writings published in newspapers, magazines, pamphlets, and books, from the time of his highƯschool days through 1957. It includes both the fiction (novels, short stories, one poem, and one play) and the nonfiction (essays, articles, statements, manifestoes, newspaper columns, etc.), and in many cases descriptions of these writing are appended when deemed necessary. As a further aid to students and researchers, Branch has listed many reprints and dates of writing for the individual short stories and has provided two appendices giving foreign editions of books and tape recordings of unpublished speeches. This detailed bibliography, the first on Farrell ever printed, is supplemented by a preface by Farrell and a foreword by the author. Edgar Branch has directed his attention to the more inaccessible of Farrell's writings and to the clarification of the voluminous abundance of written material that Farrell has produced. Through this book it is possible to trace Farrell's fluctuating status as a writer, his shifting position among editors, critics, and readers. The data included other clues to the evolution and growth of his ideas and relationships with his contemporaries, providing insight into his changing political affiliations and the motivation and development of his fiction. A Bibliography of]ames T. Farrell's Writings will be a valuable practical aid to scholars and students of literature and Americana, for it makes available a scholarly compilation of the extensive list of writings by one of America's most distinguished and controversial contemporary writers